Effect of inulin, fructo-oligosaccharide, trehalose or maltodextrin (M10 and M30) on the physicochemical and sensory properties of dark compound chocolate. (September 2021) - Lim, Pei Yiin; Wong, Keat Yi; Thoo, Yin Yin; Siow, Lee Fong
Abstract: The sucrose-free dark chocolate development is receiving attention due to increasing market demand for foods with reduced sugar. This study aimed to determine the physical and sensory properties, and the storage stability of sucrose-free dark compound chocolate by replacing the sucrose with inulin, Fructo-oligosaccharides (FOS), trehalose, or maltodextrin (M10 and M30) on a volume basis along with stevioside as a sweetening agent. Melting and crystallization properties, particle size, moisture content, rheological behaviour, hardness, bloom formation and sensory evaluation were examined using differential scanning calorimetry, particle size analyser, rheometer, and texture analysis, respectively. Sucrose substitution had no significant impact on the melting and crystallization behaviour in a compound chocolate model system. However, all sucrose-free dark compound chocolate displayed lower Casson viscosity, yield value and hardness than sucrose-containing dark compound chocolate, which may because the weaker particle-particle interaction in sucrose-free dark compound chocolate. Sucrose-free dark compound chocolate had lower sweetness (P < 0.05) and stronger bitterness (P < 0.05) compared to the sucrose compound chocolate. Trehalose was the most suitable sucrose replacer in dark compound chocolate because it resulted in similar rheological and sensory properties as the sucrose-containing dark compound chocolate and greater resistance to bloom formation after 12 weeks of storage. Highlights: Alternative sweeteners have limited influence on the thermal properties of CBS. Alternative sweeteners increase bitterness and aftertaste in compound chocolate. Trehalose or maltodextrin have greater resistance against chocolate bloom. Trehalose resembles the rheology of sucrose-contained dark compound chocolate.